Muqaran Method: The Concept of Quranic Interpretation in Islamic Legal Discourse - Muhammad Fardhannajmi Aji; Dea Putri Ananda; Eliyani; Lutfia Eka Ramadhani (Mir'ah: Family Law and Legal Culture, 2025)
This research focuses on the source of Islamic teachings, which is based on the Qur'an and sunah (hadith) as the foundation pillar where the Qur'an is the holy book of Muslims and the sunah is all the actions of the prophet and the hadith are all the words of the prophet that are narrated. Interpretation techniques on the Qur'an must be seen in terms of the muqaran method in the study of the history of Islamic law. The research method used is normative method with descriptive analysis approach. The results of research on historical studies of the muqaran method in the interpretation of the Qur'an include the 16th, 17th centuries to the current civilization. With different periods and scholars who interpret from century to century with various models of interpretation carried out by scholars such as character research models, thematic research models, ancient manuscript research models (philology), living Qur'an research models and comparative research models and criticism given to literalistic interpretations in order to know the direct meaning of the verses of the Qur'an.